PENGARUH ELECTRONIC WORD OF MOUTH, DAYA TARIK DAN LOKASI TERHADAP MINAT BERKUNJUNG WISATAWAN DI DESA TETE BATU KABUPATEN LOMBOK TIMUR - Anna Apriana Hidayanti; Lalu Masyhudi (Jurnal Inovasi Penelitian, 2020)
This research is aimed to determining the effect of electronic word of mouth, attractiveness and location simultaneously and partially affect of interest visiting Tete Batu Village, East Lombok. This research is associative research. The population of this study is all visitors in Tete Batu Village. The sample was 40 respondents. The technique of data collections were questionnaires and analyzing data through Multiple Linear Regression analysis. The results of multiple linear regression analysis obtained the formula Y = 0.429 + 0.705X1 + 0.175X2 +0.013X3 + e. Based on the hypothesis test were simultaneously the three independent variables significantly influence the interest of tourists visiting Tete Batu Village. Partially, electronic word of mouth (X1) has a positive and significant effect on the interest of visiting tourist; this could be seen from t count of 10.920, it was more than the t table value of 1.688. Attractiveness (X2) has a positive and significant effect on the interest of visiting tourists; this could be seen from the t count of 2.252, it was more than the t table value of 1.688. The location variable (X3) didn’t have any significant effect on tourist visiting, and showed that the results of the coefficient of multiple linear determination (R2) of 0.750 or75%. This means that t e degree of influence of the independent variable (X) on the variable (Y) is 75%.